La evaluación económica de los progresos técnicos y su utilización para la elección de un programa de investigación científica - Jean-Marie Martin (Económica, 1966)
When they discovered the role that technical and scientific investigation (R S T) can play in their economic development, a great number of nations realized that they could not multiply their efforts in every direction, therefore they decided to plan their investigations. The author wants to show above all, that semi-industrialized countries cannot leave the monopoly of the R S T to fully industrialized countries only. Such a choice his on the nature, considered indispensable, of the technical advancements; on the differences of natural and human faculties from one continent to another; on the specific role of the R S T in connection with learning and industry. An R S T effort is not thought of but planned. When some of the difficulties found in this way are fully analysed, the author sketches the prospects and principal lines of a method to evaluate the technical advances economically and to choose an investigation program.